Integration of fungicides and Trichoderma viride for management of seedling blight disease of apple caused by Sclerotium rolfsii - A.K. GUPTA*, KISHORE KHOSLA and (Indian Phytopathology, 2008)
In recent years, seedling blight caused by Sclerotium roltsii Sacco has emerged as a serious constraint in raising healthy apple nursery plants. At present, there is no resistant rootstock against this disease. Application of recommended fungicides alone also does not provide effective control of this disease. Therefore, in the present investigation commonly used fungicides and native isolates of Trichoderma were screened for inhibition of S. roltsii in vitro. Carbendazim (0.05%), benomyl (0.05%), hexaconazole (0.1%), difenoconazole (0.1%), thiram (0.2%) and mancozeb (0.4%) completely inhibited the growth and sclerotial formation of the pathogen. Trichoderma viride resulted in 73.3 per cent inhibition with minimum colony diameter (1.2 cm) of the pathogen. Among various fungicides tested at recommended doses for its effect on the growth and sporulation of Trichoderma viride, minimum lethal effects were observed in mancozeb (0.4%) followed by thiram (0.4%) and hexaconazole (0.1%). Fungicides viz., hexaconazole (0.1%) and thiram (0.4%) as soil drench were further tested alone and in combination with talc based formulation of Trichoderma viride in field. Minimum incidence of seedling blight (4.72%) was observed in thiram (0.4%) + T. viride (0.5%) as compared to control (37.89%).